2012
DOI: 10.1080/02635143.2012.738420
|View full text |Cite
|
Sign up to set email alerts
|

A matter of interpretation: developing primary pupils’ enquiry skills using position-linked datalogging

Abstract: This article reports on an evaluation study of a two-phase project involving 16 primary schools in England, seeking to develop the use of position-linked datalogging with pupils aged 9-10 years and hence improve their data interpretation skills. The study found that datalogging had become a regular feature of practical science in nearly all project schools up to 30 months after the end of the project, but that the use of position-linked logging had not been sustained. Whilst there is evidence of pupils develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Sorgulamaya dayalı öğrenmenin, akademik başarı, derse yönelik tutum, bilimsel süreç becerileri, bilimsel işlem becerileri vb. gibi değişkenler üzerinde olumlu etkileri olduğu ortaya konmuştur (Akben, 2011;Aydoğdu, 2009;Balım, İnel ve Evrekli, 2008;Budak Bayır, 2008;Chin ve Osborne, 2008;Çeliksöz, 2012;Davies, Collier ve Howe, 2012;Duban, 2008;Erdoğan, 2005;Gençtürk, 2004;Gül, 2011;Güngör Seyhan, 2008;İnel Ekici, 2017;Kara, 2008;Köksal, 2008;Küçük, 2012;Sağlam, 2012;Sözen, 2010;Şen, 2010;Taşkoyan, 2008;Tatar, 2006;Timur, 2005;Van Zee, Iwasyk, Kurose, Simpson ve Wild, 2001). Yaşar ve Duban (2009) ise SDÖ yaklaşımına yönelik öğrenci görüşlerini incelemişlerdir.…”
Section: Introductionunclassified
“…Sorgulamaya dayalı öğrenmenin, akademik başarı, derse yönelik tutum, bilimsel süreç becerileri, bilimsel işlem becerileri vb. gibi değişkenler üzerinde olumlu etkileri olduğu ortaya konmuştur (Akben, 2011;Aydoğdu, 2009;Balım, İnel ve Evrekli, 2008;Budak Bayır, 2008;Chin ve Osborne, 2008;Çeliksöz, 2012;Davies, Collier ve Howe, 2012;Duban, 2008;Erdoğan, 2005;Gençtürk, 2004;Gül, 2011;Güngör Seyhan, 2008;İnel Ekici, 2017;Kara, 2008;Köksal, 2008;Küçük, 2012;Sağlam, 2012;Sözen, 2010;Şen, 2010;Taşkoyan, 2008;Tatar, 2006;Timur, 2005;Van Zee, Iwasyk, Kurose, Simpson ve Wild, 2001). Yaşar ve Duban (2009) ise SDÖ yaklaşımına yönelik öğrenci görüşlerini incelemişlerdir.…”
Section: Introductionunclassified
“…In literature, inquiry-based teaching has been applied in many courses and the efficacy of this teaching method has been examined in terms of different variables considered. It was found that inquiry-based teaching increased academic achievement, enabled students to develop positive attitudes for courses, ensured the permanence of information, developed logical thinking skills and scientific data processing skills and scientific process skills (Bağcaz, 2009;Balım et al, 2008;Budak Bayır, 2008;Çeliksöz, 2012;Davies et al, 2012;Duban, 2008;Erdoğan, 2005;Evrekli, 2010;Evren, 2012;Gençtürk, 2004;Güngör Seyhan, 2008;Kara, 2008;Küçük, 2012;Sağlam, 2012;Sözen, 2010;Şen, 2010;Taşkoyan, 2008;Timur, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…National Research Council 2006;Shultz et al 2008) and GPS (e.g. Cyvin 2013;Davies et al 2012) in the teaching of GIS (Re)Connecting spatial literacy with children's geographies: GPS, Google Earth and children's everyday lives 4 (Geographical Information Science) and spatial literacy skills (e.g. Baker et al 2015;Patterson 2007).…”
Section: Introductionmentioning
confidence: 99%